Motivation: A Challenge for Oil and Gas Industry: Examining the Impact of Continuous Learning and Motivation on Employees in the Oil and Gas Industry (Journal of Advances and Scholarly Researches in Allied Education, 2017)
Continuous learning figures out how to learn. Commonly, this includes creating aptitudes in reflection, which is the capacity to constantly ask and consider involvement to make determinations and experiences. It additionally includes the capacity to conceptualize the learning procedure. Persistent learning is frequently connected with the ideas of frameworks considering and authoritative learning. This paper studies about employees learning and motivation in oil and gas industry.